The nucleotide sequence of tobacco vein mottling virus RNA. - Domier, L L (1986)
The nucleotide sequence of the RNA of tobacco vein mottling virus, a member of the potyvirus group, was determined. The RNA was found to be 9471 residues in length, excluding a 3'-terminal poly(A) tail. The first three AUG codons from the 5'-terminus were followed by in-frame termination codons. The fourth, at position 206, was the beginning of an open reading frame of 9015 residues which could encode a polyprotein of 340 kDa. No other long open reading frames were present in the sequence or its complement. This AUG was present in the sequence AGGCCAUG, which is similar to the consensus initiation sequence shared by most eukaryotic mRNAs. The chemically-determined amino acid compositions of the helper component and coat proteins were similar to those predicted from the nucleotide sequence. Amino acid sequencing of coat protein from which an amino-terminal peptide had been removed allowed exact location of the coat protein cistron. A consensus sequence of V-(R or K)-F-Q was found on the N-terminal sides of proposed cleavage sites for proteolytic processing of the polyprotein.